Systematic Review of Sustainable Competitive Advantage Factors of SMEs in The Creative Industry - Triwulandari Satitidjati Dewayana; Akbar Gunawan; Kadarsah Suryadi; Iveline Anne Marie (Logistic and Operation Management Research (LOMR), 2025)
A sustainable competitive advantage refers to a combination of characteristics and capabilities that allow a business to fulfill customer needs more effectively than its competitors. It encompasses elements that enable a company to produce goods or services of superior quality or at a lower cost than others. These advantages help businesses achieve higher sales or profit margins in the market. This literature review aims to examine and identify various factors contributing to the development of sustainable competitive advantage in the creative industry, a topic that has gained significant importance and widespread attention. This research employs a systematic literature review (SLR) approach to investigate these factors in the context of creative industries. Using the SLR approach and the PRISMA framework, this research identified, evaluated, and synthesized 27 relevant articles from the Scopus and IEEE Xplore databases, published between 2014 and 2024. These articles contain results about the factors and problems that can influence sustainable competitive advantage in creative industries with relevant fields, such as social, economic, and technical. A total of 19 factors were found that influence sustainable competitive advantage.  All these factors are important, but production quality, environmental friendliness, finance, innovation, consumer behavior, and human resources are the most prominent. This meta-analysis provides valuable insights and serves as a foundation for advancing efforts to promote the implementation of competitive advantage practices.